On the phenomenology of a two-Higgs-doublet model with maximal CP symmetry at the LHC: part II : radiative effects - Maniatis, Markos; Nachtmann, Otto (Journal of high energy physics, 2010)
The processes pp̄ and pp → γ + heavy-flavour jet(s) + X are studied in the framework of a special two-Higgs-doublet model, the MCPM. As distinguishing feature of this model we find that radiative Higgs-boson production and decay lead to heavy flavour c jets but no b jets in the above processes. Thus, the prediction is that b jets should be given by the normal QCD processes whereas for c jets an excess over the QCD expectation should occur. We present results both for Tevatron and LHC energies.
Gesehen am 04.05.2023